Miloš Crnjanski`s metahistorical projection of war - Andrejević, Danica T.; Andrejević, Ana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
The Great War triggered the establishment of the Serbian literary avant-garde, which was determined against tradition, history, and conventional aesthetics. With a completely new expression, writers of the literary avant-garde articulated the change of consciousness about the world, metamorphosis of the narrative structure of the text, and the modernization of the novelistic form. In the context of the European literature, as well as the Anglo-American, the return of the soldiers from the war was the prominent topic in the works of the so-called "Lost generation" (Gertrude Stein, E. Hemingway and S. Fitzgerald). The themes of war also occupied writers such as W. Faulkner, T. Wolfe and H. Miller. The greatest poet of the Serbian literature between the two world wars, Miloš Crnjanski, presented the suprahistorical projection of the war and considered the return of the soldiers to be the saddest event in a man’s life. The first Serbian modern, lyrical novel, "Journal of Čarnojević" (Dnevnik o Čarnojeviću), gives a metaphysical picture of history and intimately understood picture of the wartime world, nation and being. This paper follows Crnjanski`s views on history and war through the main character, Petar Rajić, and his counterpart of sorts, Čarnojević. Poetics of this modernistic text rests on the fictionalization of fact, metaphorization of war and aestheticization of history. As a resigned pacifist and disappointed melancholic, Rajić perceives the war completely anti-traditionally in comparison to a hero of a classical history novel. Visualization of events and the relativization of war and chronotope in the lyrical discourse of Miloš Crnjanski allow history to disperse into poetry, into the essence of being and the ontological plane of this metahistorical novel.
Keywords: sumatraism; war; history; Miloš Crnjanski